PROTECTIVE ROLE OF SPIRULINA ON HEMATOLOGY AND HEPATOTOXICITY INDUCED BY CUSO4 AND CUO NANOPARTICLES IN OREOCHROMIS NILOTICUS - Rasheeka Rasheed, Amara Akhtar, Rohma Talha, Babar Khan, Rabeel Mehmood, Awais Amin, Mubeen Sabir, Muhammad Ahmed Saqib (Chelonian Research Foundation, 2024)
Copper toxicity poses significant risks to fish. Spirulina platensis a cyanobacterium (protist), has shown protective properties against metal-induced toxicity in various species. This study investigated the prophylactic role of Spirulina platensis in Nile tilapia (Oreochromis niloticus) against the toxicity of copper sulfate (CuSO₄) and Copper oxide nanoparticles (CuO-NPs). Over 15 days, tilapia were divided into five groups: For this purpose, fish were divided into five treatments. T0 was a controlled treatment. T1 was treated with 15mgl-1 CuO-NPs. T2 was fed with 2.5gkg-1 Spirulina and 15mgl-1 CuO-NPs. T3 was treated with 15mgl-1 CuSO4. T4 was treated with 2.5gkg-1 Spirulina and exposed to 15mgl-1 CuSO4. CuSO4 and CuO-NPs were given for the last 15 days and Spirulina was given on the first day of the trial in T2 and T4. The results showed that both CuSO₄ and CuO-NPs significantly increased biochemical parameters like total ALP, ALT and AST. Hematological disturbances and erythrocyte count along with histopathological damage to organs like the liver were also observed. However, Spirulina supplementation notably mitigated these adverse effects, reducing and preserving tissue integrity and normalizing all parameters. This study highlights the species-specific protective effects of the agent and suggests that Spirulina may offer protection against copper-induced toxicity. Future research is needed to explore the long-term impacts and underlying mechanisms of these agents, along with their optimal dosages for enhancing fish health in aquaculture.